MODEL FOR ENERGY-EFFICIENCY AUDIT AND MONITORING OF THE COAL PROCESSING SYSTEMS IN THE FOSSIL-FUEL POWER PLANTS - OGNYAN DINOLOV (Journal of Engineering Studies and Research)
Based on interpretation of existing developments, an aggregate model for energy audit and monitoring of the electric-energy efficiency in the coal processing systems in the fossil-fuel power plants is developed. The model takes into account the nominal power capacities of the available drives, by which the usability of the installed power capacity is considered and the interdependence between the power consumed and the relative consumption is avoided in determining the aggregate relative electric-power consumption. The model is justified by conducting an energy audit of a typical coal processing systems in operation. The results of this research can be a basis for the development of models of systems and systems for qualitatively new monitoring of the overall electric-energy efficiency in the fossil-fuel power plants.